2020
DOI: 10.1111/tmi.13471
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and temporal tendency of mortality related to Chagas disease in an endemic area of northeastern Brazil

Abstract: objective To analyse spatial patterns and the temporal tendency of mortality related to Chagas disease, in order to identify priority control areas in the state of Sergipe, Northeast Brazil. methods We conducted an ecological and time-series study with spatial analysis techniques on deaths from Chagas disease in the state of Sergipe (1996-2016). We used data from the Mortality Information System (SIM). The temporal analysis was performed using a statistical technique capable of describing changes in the trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…Notwithstanding, the country exhibits serious social inequalities, as people living in extreme poverty, illiteracy, household clusters, and areas with no access to safe-drinking water and sewage system, mainly in slums (IBGE, 2021). Hence, Brazil is endemic for many neglected diseases as Chagas disease ( Góes et al, 2020 ), leprosy ( Souza et al, 2020 ; Damasceno et al, 2021 ), leishmaniasis ( Ribeiro et al, 2021 ), schistosomiasis ( Paz et al, 2020 ; Silva da Paz et al, 2021 ), and TB ( Lima et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Notwithstanding, the country exhibits serious social inequalities, as people living in extreme poverty, illiteracy, household clusters, and areas with no access to safe-drinking water and sewage system, mainly in slums (IBGE, 2021). Hence, Brazil is endemic for many neglected diseases as Chagas disease ( Góes et al, 2020 ), leprosy ( Souza et al, 2020 ; Damasceno et al, 2021 ), leishmaniasis ( Ribeiro et al, 2021 ), schistosomiasis ( Paz et al, 2020 ; Silva da Paz et al, 2021 ), and TB ( Lima et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…For political and operational purposes, the states are grouped into five regions (North, Northeast, Southeast, South, and Midwest) with distinct geographic, economic and cultural characteristics ( Supplementary material 1 ). 15 Importantly, despite being the 12th largest economy in the world (US$ 1.434 trillion in 2021), Brazil has serious social inequalities and it is endemic for several NTDs, such as Leishmaniasis, 16 Chagas Disease, 17 Schistosomiasis 18 , 19 and Leprosy. 20 , 21 …”
Section: Methodsmentioning
confidence: 99%
“…Some information is available from different series of cohorts and mortality registries, where a range of baseline aspects have been evaluated in various countries. These studies have analyzed different aspects such as rates as well as temporal and geospatial trends of mortality due to CD in general or specifically chagasic cardiomyopathy [ 23 , 24 , 25 , 26 , 27 ]. Other studies analyze excess preventable mortality from the disease and the geo-economic implications of the problem [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…While assessing productivity losses was beyond the scope of the study, we observed that 32 of the 56 patients who died (57.1%) were under 60 years old; thus, in line with an increased loss in productive life-years. Regarding the analysis of mortality in endemic areas in Latin America, several studies in Brazil, Colombia, Chile and Ecuador have examined the spatial patterns of CD mortality, enabling the identification of priority areas for health services planning and control strategies [ 25 , 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation